Are Kenyans Suffering from Procurement Nightmare Culture? - Jackson Ndolo; Eunice G. Njagi (International Journal of Supply Chain Management, 2014)
The public procurement system in Kenya has never been subjected to negative publicity as in the recent past. This has been so due to the over reported mega corruption related cases though in many cases no evidence has ever been produced before any of the statutory procurement bodies. Is it a case of wind blowing in place of whistle blowing? Or are Kenyans suffering from procurement nightmare culture? This article therefore explores the state of procurement system in the country and concludes that despite public outcry in many cases the public cares less about facts since most of the procurement corruption scandals in the Kenyan scene are just media creations and politically engineered to malign one side of the political divide as politicians seek to outwit each other.